Genotoxicity of purine acyclic nucleotide analogs - Otová, B; Holý, A; Votruba, I; Sladká, M; Bílá, V; Mejsnarová, B; Lesková, V (Folia biologica, 1997)
The genotoxic and embryotoxic effects of phosphonomethoxyalkylpurines, a new group of antiviral agents, decrease in the following order: PMEG > PMEthioG > PMEDAP > PMEA > (R)-PMPDAP = (R)-PMPA. Results of the present study are fully consistent with the previously found efficacy of their diphosphates to inhibit the replicative DNA polymerases. The marked genotoxicity of PMEG and PMEthioG is comparable to that of mitomycin C, whereas the moderate genotoxicity of PMEA is comparable to that of AZT. (R)-PMPDAP and (R)-PMPA did not induce any structural aberrations of chromosomes under the experimental conditions.
Keywords: mutageny; Adenine; Cell Line; Mutagenicity Tests; Rats; Thioguanine; teratogeny; guanin; Guanine; testy genotoxicity; organofosforové sloučeniny; mužské pohlaví; adenin; antivirové látky; Mutagens; krysa rodu Rattus; Organophosphonates; Organophosphorus Compounds; ženské pohlaví; Rats, Inbred BN; zvířata; Humans; Tenofovir; potkani inbrední BN; thioguanin; Purines; puriny; potkani inbrední LEW; molekulární struktura; Rats, Inbred Lew; buněčné linie; Antiviral Agents; Female; tenofovir; organofosfonáty; Teratogens; lidé; Male; Molecular Structure; Animals